Preparation method of bulk hydrotreating catalyst
Through the preparation method of bulk hydrorefining catalysts using core-shell structure, the problems of uneven distribution of active metals and unsatisfactory pore structure in the existing catalysts are solved, efficient hydrodesulfurization and denitrification properties are achieved, and the preparation is reduced. cost.
Patent Information
- Application Number
- CN202210393511.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-04-15
AI Technical Summary
The existing bulk hydrogenation catalysts have problems such as uneven distribution of active metals, unsatisfactory pore structure, high preparation costs and large wastewater treatment costs.
The preparation method of bulk hydrorefining catalyst with core-shell structure is adopted, and a catalyst with uniform distribution of active metals and optimized pore structure is generated through the first gel forming reaction and the second gel forming reaction, and the preparation cost is reduced by desalting treatment.
The efficient hydrodesulfurization and nitrogen removal performance of the catalyst is achieved, the preparation cost is reduced, and the process is clean and pollution-free.
Smart Images

Figure CN116943680B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst preparation, and in particular relates to a method for preparing a bulk hydrorefining catalyst with a core-shell structure. The hydrorefining catalyst is suitable for processes such as hydrodesulfurization and denitrogenation of distillate oil. Background Art
[0002] Traditional supported hydrogenation catalysts are limited by the pore structure of the carrier, and the active metal loading generally does not exceed 30wt%. The number of active centers that supported catalysts can provide is limited, and cannot meet the demand for significantly reducing the aromatic content of catalytic diesel. Bulk phase catalysts are currently the most active hydrogenation catalysts, with an active metal content of more than 70%. Bulk phase hydrogenation catalysts can get rid of the limitation of metal content, and the proportion of each active component in the catalyst can be arbitrarily adjusted to improve the hydrogenation performance of the catalyst. The combination of active metal components in the hydrogenation catalyst is more active than the individual components. Among the combinations of metal components, the W-Ni combination has the best hydrogenation saturation activity, and the Mo-Ni combination has the best hydrogenation denitrification performance.
[0003] During the distillate oil hydrogenation reaction, the reactant molecules pass through the catalyst pores and react on the catalyst surface they contact. The catalyst needs to have a larger pore size to facilitate the smooth passage of macromolecular reactants through the catalyst pores, which can reduce the inhibitory effect of macromolecular nitrides on the hydrodesulfurization reaction. Although the bulk hydrogenation catalyst prepared by the existing method has a high active metal content, the disordered distribution of different hydrogenation active metals causes no good coordination between the active metals. The high content of metal in the bulk catalyst is prone to excessive accumulation of metal particles, which reduces the generation of active phases and prevents the active metals from becoming hydrogenation active centers. At the same time, the matching degree between the active metals and the pores at different positions in the catalyst needs to be improved. The catalyst surface is small and the active metals are unevenly dispersed, which affects the utilization rate of the active metals of the catalyst and also increases the cost of using the catalyst.
[0004] The use of impregnation and kneading methods to prepare catalysts results in high catalyst preparation costs and large wastewater treatment costs because relatively low-priced sodium metal salt raw materials cannot be used. The coprecipitation method can use relatively low-priced sodium raw materials to prepare catalysts, which greatly reduces the catalyst preparation costs and wastewater treatment costs. However, the introduction of a large number of sodium ions makes it difficult to remove sodium ions from the catalyst. Even if the number of washings is increased (the increase in the number of washings will reduce the crushing strength of the catalyst), only the sodium ions on the surface of the catalyst can be removed. A large number of sodium ions still exist in the precipitated material. The residual sodium ions lead to poor adhesion of the material. The sodium ions that are not removed are not conducive to the formation of the catalyst pore structure, resulting in a small pore volume and pore size of the catalyst.
[0005] The existing co-precipitation method mostly uses ammonia water as a precipitant and nitrogen-containing soluble salts as raw materials. The distribution of hydrogenation active metals and the interaction between different hydrogenation active metals are improved by changing the precipitation method and gelation conditions. However, it does not solve the problems of small pore volume and specific surface area of bulk catalysts, small pore size of catalysts (pore size distribution is mainly concentrated below 8nm), large metal oxide particles in catalysts, and "ammonia nitrogen" and NO in catalyst preparation. X There are many problems such as pollution and high cost. Especially when using cheaper sodium-containing raw materials, the gel-forming materials are loose and difficult to shape, and the catalyst has many small pores.
[0006] CN106179474B discloses a high-activity bulk hydroprocessing catalyst and a preparation method thereof. A two-step method of positive addition and parallel flow is adopted to prepare a precipitate containing W, Ni and Mo, and a microporous and mesoporous composite molecular sieve is added. The catalyst has a high surface active metal content, a more uniform active metal dispersion, good coordination between active metals, and a high active metal utilization rate. At the same time, the catalyst has a reasonable pore structure, high mechanical strength, and high hydrodesulfurization and hydrodenitrogenation activity. The catalyst prepared by this method contains a molecular sieve, and a strong acidity can improve the ultra-deep desulfurization activity of the catalyst, but a cracking reaction occurs, which reduces the yield of the diesel product.
[0007] CN102451706A discloses a method for preparing a hydrogenation catalyst composition, which comprises using a sodium aluminate solution, a mixed solution containing Ni and W component salts, and CO 2 The gas reacts in parallel to generate a precipitate. CN110038581A discloses a method for preparing a hydrorefining catalyst. The hydrorefining catalyst is prepared by two-step precipitation, using sodium tungstate alkaline solution and sodium molybdate alkaline solution as precipitants. Both methods use a large amount of sodium ion-containing salt as raw material for precipitation reaction, but the precipitate generated by this method contains a certain amount of sodium ions, the metal oxide particles are relatively large, and the residual sodium ions lead to poor adhesion of the material. The residual sodium ions also make the pore volume and specific surface area of the catalyst small.
[0008] CN106513006A discloses a method for preparing a bulk phase hydrorefining catalyst, which comprises: pre-dispersing a Ni-containing compound with deionized water under an ultrasonic environment, then adding a Mo-containing compound to form a Ni-Mo fine grain structure, then adding a W-containing compound and a complexing agent for hydrothermal reaction, and then kneading and extruding the obtained active component powder with aluminum hydroxide dry glue, drying and calcining to obtain a catalyst. The catalyst prepared by the method of the present invention has uniform dispersion between different active phase grains, W source is embedded in the Ni-Mo skeleton structure, Ni-W active phase is easily wrapped by Ni-Mo active phase at the microscopic level, and is not an oxide core-shell structure at the macroscopic level, the pore volume is small, the effective active phase is not much, the metal oxide particles are large, and the removal efficiency of complex sulfur-containing compounds with high nitrogen content is limited. Summary of the invention
[0009] In view of the shortcomings of the prior art, the present invention provides a bulk hydrofining preparation method. The bulk hydrofining catalyst has a core-shell structure, the particle size distribution of the catalyst particles is concentrated, the pore volume and pore size of the catalyst are large, and it has high hydrodesulfurization and hydrodenitrogenation reaction performance, low preparation cost, clean preparation process and no pollution, and can be used in the hydrofining process of inferior distillate oil.
[0010] The preparation method of the bulk hydrotreating catalyst of the present invention comprises the following contents:
[0011] (1) subjecting a sodium hydroxide aqueous solution, a sodium molybdate solution and a solution containing nickel and silicon to a first gelling reaction, and then subjecting the solution to aging to obtain a first slurry, filtering to obtain a filter cake, and beating and mixing the filter cake with a solution containing nickel, aluminum and a polyoxyethylene nonionic surfactant to obtain a mixed slurry;
[0012] (2) Deionized water and unsaturated higher fatty acid glyceride are added to the reactor, and then sodium tungstate solution, sodium carbonate and / or sodium bicarbonate aqueous solution, and the mixed slurry obtained in step (1) are added to the reactor in parallel to carry out a second gelling reaction, and after the reaction, the second slurry is aged to generate a second slurry;
[0013] (3) aging the second slurry, separating the solid from the liquid after aging, and drying and molding the solid phase to obtain a molded product;
[0014] (4) The formed product is desalted, washed, dried and calcined to obtain a bulk hydrogenation refining catalyst.
[0015] In the method of the present invention, in the nickel-silicon solution described in step (1), the weight concentration of Ni in terms of NiO is 5 to 120 g / L, preferably 10 to 110 g / L, and the weight concentration of Si in terms of SiO 2The weight concentration is 2~80g / L, preferably 4~70g / L; when preparing nickel-silicon solutions, the nickel source generally used is one or more of nickel sulfate, nickel nitrate, and nickel chloride, and the silicon source is one or more of water glass, silica sol, etc.
[0016] In the method of the present invention, in the sodium molybdate solution described in step (1), Mo is in the form of MoO 3 The weight concentration is 5 to 110 g / L, preferably 10 to 100 g / L.
[0017] In the method of the present invention, the weight concentration of the sodium hydroxide aqueous solution in step (1) is 5% to 30%, and those skilled in the art can determine the dosage according to actual needs.
[0018] In the method of the present invention, the conditions of the first gelling reaction in step (1) are as follows: reaction temperature is 30-90°C, preferably 40-85°C, pH value is 7.0-11.0, preferably 7.2-10.0, and gelling time is 0.2-2.5 hours, preferably 0.3-2.0 hours.
[0019] In the method of the present invention, the aging conditions in step (1) are as follows: the aging temperature is 60-90° C., preferably 65-85° C., the pH value is 7.0-11.0, preferably 7.2-10.5, and the aging time is 0.3-2.5 hours, preferably 0.5-2.0 hours.
[0020] In the method of the present invention, in the solution containing nickel, aluminum and polyoxyethylene nonionic surfactant in step (1), the weight concentration of Ni in terms of NiO is 5 to 110 g / L, preferably 10 to 100 g / L, and the weight concentration of Al in terms of Al is 10 to 20 g / L. 2 O 3 The weight concentration is 2-95 g / L, preferably 5-85 g / L; the molar ratio of the polyoxyethylene nonionic surfactant to the sodium tungstate solution is 0.3-2.5:1, preferably 0.4-1.8:1.
[0021] In the method of the present invention, when preparing the Ni and Al solution in step (1), the nickel source generally used is one or more of nickel sulfate, nickel nitrate and nickel chloride, and the aluminum source is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride and aluminum acetate. The polyoxyethylene type nonionic surfactant is selected from one or more of fatty alcohol polyoxyethylene ether (C16-18 alcohol polyoxyethylene ether, C12-14 alcohol polyoxyethylene ether, oleyl alcohol polyoxyethylene ether, isomeric decanol polyoxyethylene ether, octylphenol polyoxyethylene ether, castor oil polyoxyethylene ether), alkylphenol polyoxyethylene (4, 6, 7, 9, 10, 15) ether, dodecylamine polyoxyethylene ether and the like.
[0022] In the method of the present invention, in step (1), the weight of Ni introduced through the solution containing Ni and Si accounts for 30% to 80% of the total weight of Ni in the hydrorefining catalyst obtained in step (4), preferably 35% to 78%. The weight of Ni introduced through the solution containing Ni, Al and a polyoxyethylene nonionic surfactant accounts for 20% to 70% of the total weight of Ni in the hydrorefining catalyst obtained in step (4), preferably 22% to 65%.
[0023] In the method of the present invention, in the sodium tungstate solution described in step (2), W is WO 3 The weight concentration is 4 to 140 g / L, preferably 6 to 120 g / L.
[0024] In the method of the present invention, the weight concentration of the sodium carbonate and / or sodium bicarbonate aqueous solution in step (2) is 5% to 40%. Those skilled in the art can determine the dosage according to actual needs.
[0025] In the method of the present invention, the volume ratio of the deionized water added in step (2) to the volume ratio of the first slurry in step (1) is 0.1:1 to 3:1.
[0026] In the method of the present invention, the unsaturated higher fatty acid glyceride (vegetable oil) in step (2) is one or more of peanut oil, rapeseed oil, cottonseed oil, sunflower seed oil, soybean oil, corn oil, tea oil and olive oil; the volume ratio of the unsaturated higher fatty acid glyceride to deionized water is 1:60-1:4, preferably 1:40-1:6.
[0027] In the method of the present invention, the conditions of the second gelling reaction in step (2) are as follows: the reaction temperature is 30-90°C, preferably 40-85°C, the pH value is initially controlled to be 10.0-14.0, preferably 10.5-13.5, the final pH value is 7.0-8.5, preferably 7.2-8.3, and the gelling reaction time is 0.5-6.0 hours, preferably 0.6-5.0 hours. Preferably, the pH value can be adjusted from the initial value to the final pH value by a stepwise downward adjustment method, and the stepwise downward adjustment method is to adjust the pH value to the desired value of the time, and keep the pH value of the reaction slurry constant until the next downward adjustment begins, and the number of downward adjustments is 2-10 times, preferably 2-8 times. Preferably, it is preferably kept constant for 0.1-1.2 hours after each downward adjustment. The amplitude of each downward adjustment can be the same or different, and it is preferred that the amplitude of the pH reduction in the current downward adjustment is equal to or less than the amplitude of the pH reduction in the previous downward adjustment. The time used for each downward adjustment process is from the start of the current downward adjustment to the start of the next downward adjustment, and further, is the sum of the time used for each pH value downward adjustment and the time when the pH value is constant. The time used for each downward adjustment process can be the same or different, and preferably the same time.
[0028] In the method of the present invention, the aging conditions in step (2) are as follows: aging temperature is 40 to 90° C., aging time is 1 to 5 hours, and pH value is 7.0 to 11.0. The aging is generally carried out under stirring conditions.
[0029] In the method of the present invention, the aging described in step (2) is preferably carried out in the following manner: the first step is normal pressure aging: the aging temperature is 30-90°C, preferably 40-80°C, the aging time is 1-6 hours, preferably 1.2-5 hours, and the pH value is 6.5-10.0, preferably 7.0-9.0; the second step is high pressure aging: the temperature is 100-195°C, preferably 100-190°C, the time is 0.1-3.5 hours, preferably 0.3-2.8 hours, the pressure is not less than 10 MPa, preferably 10-15 MPa, and the pH value is 10.0-13.0, preferably 10.0-12.5.
[0030] In the above process, a regular body has been generated in the material phase structure in the first step of aging. Under the action of higher temperature and pressure, the material phase changes from a regular body to an irregular body formed by irregular flakes. This structural change makes it easier for the sodium ions inside the phase to transfer to the surface of the phase, which is more conducive to the next step of desalination treatment. It is also beneficial to increase the specific surface area of the bulk catalyst, improve the pore structure, expose more active metals on the catalyst surface, and generate more hydrogenation active centers on the catalyst surface.
[0031] In the method of the present invention, the solid-liquid separation in step (3) is generally carried out by filtration, centrifugation or the like.
[0032] In the method of the present invention, the drying temperature in step (3) is 50 to 140° C., and the drying time is 0.5 to 24 hours.
[0033] In the method of the present invention, the molding process described in step (3) is well known in the field of catalyst preparation. During the extrusion molding process, an extrusion aid and a peptizing agent are generally added. The extrusion aid can be one or more of sesbania powder, carbon black, graphite powder or cellulose, etc. The peptizing agent is generally an acid solution containing one or more of hydrochloric acid, sulfuric acid, acetic acid, etc. The amount of the extrusion aid accounts for 1wt% to 10wt% of the total material dry basis. The catalyst of the present invention can be prepared into the shape of flakes, spheres, cylindrical strips and special-shaped strips (three-leaf clover, four-leaf clover) as needed.
[0034] In the method of the present invention, the desalination treatment process described in step (4) is: first curing, and then washing to remove the salt precipitated on the surface of the molded product, the curing conditions are a temperature of 5 to 100°C, preferably a temperature of 10 to 90°C, and a time of 10 to 100 hours, preferably 24 to 90 hours.
[0035] In the method of the present invention, the desalination treatment described in step (4) is preferably carried out in the following manner: in the first stage, the temperature is 60 to 90° C., and the curing time is 5 to 60 hours, preferably 8 to 55 hours, so that the hydrated sodium ions are precipitated and vacancies are retained; in the second stage, the temperature is 10 to 30° C., and the time is 1 to 48 hours, preferably 2 to 42 hours, so that the vacancies are retained and shrunk, so that the pore volume of the catalyst is increased and the catalyst has good mechanical strength, and then the precipitated salt is washed away, and the washing process uses a solvent such as water and ethanol that has a good solubility for sodium salt.
[0036] In the method of the present invention, the washing, drying and roasting in step (4) can be carried out under conventional conditions in the art. The drying conditions are as follows: drying at 40-150°C for 1-48 hours, preferably drying at 50-120°C for 4-36 hours. The roasting conditions are as follows: roasting at 350-650°C for 1-24 hours, preferably roasting at 400-600°C for 2-12 hours. Washing is generally carried out with deionized water or ethanol solution until neutral.
[0037] The present invention also provides a bulk hydrorefining catalyst, which is a core-shell structure composite amorphous oxide particle, wherein the core phase is an amorphous composite oxide containing molybdenum, nickel and silicon, and the shell phase is an amorphous composite oxide containing tungsten, nickel and aluminum; the catalyst of the present invention can be in the form of flakes, spheres, cylindrical bars and shaped bars (three-leaf clover, four-leaf clover) as needed, preferably cylindrical bars and shaped bars (three-leaf clover, four-leaf clover). The average particle size of the catalyst particles is 8-13nm. Preferably, the particle size distribution of the catalyst particles is as follows: the number of particles with a particle size less than 7nm accounts for 2%-15% of the total number of particles, the number of particles with a particle size of 7nm-13nm accounts for 66%-88% of the total number of particles, and the number of particles with a particle size greater than 13nm accounts for 3%-21% of the total number of particles.
[0038] In the catalyst of the present invention, based on the mass of the core-shell structured composite oxide particles, the core phase accounts for 20% to 90%, preferably 25% to 88%, and the shell phase accounts for 10% to 80%, preferably 12% to 75%.
[0039] In the catalyst of the present invention, the molar ratio of molybdenum to nickel atoms in the core phase is 1:28 to 12:1, preferably 1:22 to 10:1, and the content of silicon is expressed as SiO 2 It accounts for 2% to 38% of the mass of the hydrotreating catalyst, preferably 4% to 36%.
[0040] In the catalyst of the present invention, the molar ratio of tungsten to nickel atoms in the shell phase is 1:22-8:1, preferably 1:20-5:1, and the content of aluminum is expressed as Al 2 O 3 It accounts for 5% to 36% of the mass of the hydrotreating catalyst, preferably 7% to 34%.
[0041] In the catalyst of the present invention, the mass of NiO in the core phase accounts for 30% to 80% of the total mass of NiO in the hydrorefining catalyst, and the mass of NiO in the shell phase accounts for 20% to 70% of the total mass of NiO in the hydrorefining catalyst.
[0042] The Na in the catalyst of the present invention 2 The O content is less than 0.12%, preferably less than 0.1%.
[0043] In the catalyst of the present invention, the properties of the hydrotreating catalyst are as follows: the specific surface area is 180~700m 2 / g, pore volume is 0.30~0.90mL / g. The pore size distribution of the bulk hydrorefining catalyst of the present invention is as follows: the pore volume occupied by pores with a diameter of less than 4nm accounts for 1%~10% of the total pore volume, the pore volume occupied by pores with a diameter of 4~10nm accounts for 12%~40% of the total pore volume, the pore volume occupied by pores with a diameter of 10~15nm accounts for 22%~56% of the total pore volume, and the pore volume of pores with a diameter of more than 15nm accounts for 18%~45% of the total pore volume; the preferred pore size distribution is as follows: the pore volume occupied by pores with a diameter of less than 4nm accounts for 2%~8% of the total pore volume, the pore volume occupied by pores with a diameter of 4~10nm accounts for 14%~36% of the total pore volume, the pore volume occupied by pores with a diameter of 10~15nm accounts for 24%~54% of the total pore volume, and the pore volume of pores with a diameter of more than 15nm accounts for 20%~42% of the total pore volume.
[0044] The bulk hydrofining catalyst of the present invention is used in the hydrofining reaction of inferior distillate oil, wherein the inferior distillate oil is catalytic diesel, coker diesel, mixed diesel (mixture of catalytic diesel, coker diesel and straight-run diesel, with the mass percentage of catalytic diesel greater than 30%) and vacuum distillate.
[0045] Furthermore, the conditions for the hydrofining reaction of the inferior distillate oil are as follows: reaction temperature is 330-400°C, reaction pressure is 2.5-17MPa, hydrogen-oil volume ratio is 250:1-1200:1, liquid hourly volume space velocity is 0.3-5.0h -1 .
[0046] Compared with the prior art, the present invention has the following advantages:
[0047] 1. The hydrorefining catalyst of the present invention improves the distribution state of active metals at the nano level, that is, it is mainly composed of composite oxide particles containing molybdenum, nickel and silicon coated with composite oxide containing tungsten, nickel and aluminum. This coating structure is different from the structure at the macro level (such as millimeter level). The structure of the catalytic material is controlled at the micro level, so that the overall performance of the catalyst can be broken through, the hydrodesulfurization performance of the catalyst is improved, and a certain amount of acid centers are formed at the junction of the core-shell structure of the catalyst, so that the catalyst can eliminate steric hindrance while performing hydrodesulfurization reaction, and reduce the occurrence of side reactions such as excessive cracking, so that when the distillate oil raw materials containing sulfur and nitrogen (especially the distillate oil raw materials containing sulfur and nitrogen that are difficult to remove) contact with the hydrorefining catalyst of the present invention, the desulfurization and denitrification activities are significantly improved, and at the same time, the cracking reaction of the diesel fraction is reduced, and the diesel yield is avoided. In addition, the catalyst of the present invention can reduce the content of active metals while ensuring the desulfurization and denitrification activities, thereby reducing the preparation cost of the catalyst.
[0048] 2. In the method of the present invention, a molybdenum-nickel-silicon aged slurry is first prepared, and then the filter cake generated by the first gelation reaction, the polyoxyethylene nonionic surfactant and the solution containing Ni and Al are mixed and subjected to a second gelation reaction in a reactor containing water and an oily liquid, so that tungsten and nickel are uniformly and orderly precipitated on the molybdenum-nickel grains. The particle size of the obtained core-shell composite oxide particles is more uniform and the particle shape is regular, that is, the nano-scale core-shell structure mainly composed of composite oxide particles containing tungsten, nickel and aluminum coated with composite oxide particles containing molybdenum, nickel and silicon. This coating structure is different from the structure at the macroscopic level (such as millimeter level). The structure of the catalytic material is controlled at the microscopic level, and the interaction between the active metals at the junction of the core-shell structure is enhanced. At the same time, the addition of the polyoxyethylene nonionic surfactant promotes the dispersion of Ni and W in the shell phase, avoids the disordered growth of the core-shell structure, and the particle size of the obtained core-shell composite oxide particles is further uniform.
[0049] 3. The method of the present invention uses soluble sodium salt as raw material at the same time, first retains the sodium salt in the material, and then desalts the formed material to remove the precipitated sodium salt. In this process, due to the occupation of sodium salt in the forming process, the vacancy after sodium removal increases the pore volume and pore size of the catalyst, so that the active metal of the catalyst with a core-shell structure is better matched with the structure, the diffusion performance of the catalyst is improved, and the desulfurization and denitrification capabilities of the bulk catalyst when processing heavy diesel distillate oil are greatly improved. In the catalyst preparation process, washing is only required during the desalting process, which reduces the number of washing times in the conventional catalyst preparation process and reduces the amount of water. At the same time, the core-shell structure of the catalyst of the present invention further promotes the precipitation of sodium salt during the desalting process. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is the TEM image of catalyst B obtained in Example 2. DETAILED DESCRIPTION
[0051] In the present invention, the specific surface area and pore volume are measured by low temperature liquid nitrogen adsorption method, and the mechanical strength is measured by lateral pressure method. The specific surface area, pore volume and pore size distribution are measured by ASAP-2405 BET nitrogen adsorption instrument; the crushing strength of the catalyst is measured by ZQJ-2 intelligent particle strength testing machine.
[0052] In the present invention, in the core-shell composite oxide particles, the metal content in the composite oxide in the core and the shell and the thickness of the shell are measured by TEM transmission electron microscope (Japan JSM-2100). Among them, the method for determining the metal content in the composite oxide in the core and the shell is as follows: the core-shell composite oxide particles are uniformly mixed with liquid epoxy resin, and then an appropriate amount of curing agent is added, and the mixture is heated and cured after being stirred evenly to form solid particles. The solid particles are cut into thin slices with a thickness of 5-20nm by an ultrathin slicer, and the obtained slices are placed in a transmission electron microscope for observation to find a core-shell structure (cross section) with a clear interface. The diameter of the electron beam is adjusted by a condenser so that its diameter basically covers the outline of the entire core-shell structure, and the energy spectrum EDS spectrum is collected to record the intensity of the main energy peak, which corresponds to the actual content of each element in the known feed and the energy peak intensity of each element. The electron beam diameter is adjusted so that it is smaller than or close to the core or shell size, and the metal content in the composite oxide in the core and the shell at this time is calculated according to the energy peak intensity corresponding to the element, compared with the peak intensity under full coverage and the corresponding actual value. In the core-shell structure, the shell thickness is identified and measured from the transmission electron microscope image, and the ratio of the shell thickness to the total core-shell thickness is the average value obtained by measuring 40 to 100 core-shell particles.
[0053] In the present invention, wt% refers to mass fraction, and v% refers to volume fraction.
[0054] Example 1
[0055] Add nickel chloride and water glass to a dissolving tank 1 filled with deionized water to prepare a solution containing Ni and Si. The concentration of Ni in the solution is 28 g / L in terms of NiO and 28 g / L in terms of SiO. 2 The weight concentration is 36g / L. Nickel chloride, aluminum chloride, and octylphenol polyoxyethylene ether solutions are added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni, Al, and octylphenol polyoxyethylene ether. The weight concentration of Ni in the solution containing Ni, Al, and octylphenol polyoxyethylene ether is 24g / L in terms of NiO, and the weight concentration of Al in terms of AlO is 24g / L. 2 O 3The weight concentration is 36g / L, and the molar ratio of the moles of octylphenol polyoxyethylene ether to the W in the sodium tungstate solution is 0.8. Among them, the mass ratio of Ni in the solution containing Ni and Si used in the reaction of this embodiment to Ni in the solution containing Ni, Al and octylphenol polyoxyethylene ether used is 14:12. The solution containing Ni and Si is placed in the reaction tank 1, and the sodium hydroxide solution (weight concentration is 12%) and the sodium molybdate solution (Mo is in the form of MoO 3 The weight concentration of the reaction mixture is 36 g / L) and is dropped into the reaction tank 1 for the first gelling reaction. The gelling temperature is maintained at 62°C. The pH value is controlled at 7.8 at the end of the reaction and the gelling time is controlled at 1.2 hours. After the reaction is completed, aging is performed at 78°C and the aging pH value is controlled at 7.5 for 1.8 hours. After obtaining the first slurry, the filter cake is slurried and mixed evenly with the solution containing Ni, Al and octylphenol polyoxyethylene ether. 800 mL of deionized water and 60 mL of rapeseed oil are added to the reaction tank 2, and then a 10 wt% sodium carbonate solution, a first slurry filter cake, a solution containing Ni, Al and octylphenol polyoxyethylene ether, and a sodium tungstate solution (W in WO) are mixed. 3 The weight concentration of the measured solution is 40g / L) and then added to the reaction tank 2 for the second gelling reaction. The gelling temperature is maintained at 60℃, and the pH value is initially controlled to be 13.0. The pH value is adjusted down 6 times to adjust the final pH value to 7.6 at the end. The pH value is adjusted down to 0.9 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry is kept constant for 10 minutes. After the second gelling reaction, aging begins. The aging temperature is 78℃, the pH value is controlled at 8.0, and the aging time is 2.5 hours to obtain the second slurry. The aged slurry is filtered, the filter cake is dried at 100℃ for 7 hours, rolled, and extruded into a clover shape. After the formed strips are cured at a temperature of 70℃ for 50 hours, the temperature is reduced to 20℃, and the curing is continued for 30 hours. Wash with deionized water at room temperature until neutral. The wet strips are then dried at 100℃ for 12.0 hours, and the dried material is calcined at 500℃ for 4 hours to obtain catalyst A. The composition and main properties of the catalyst are shown in Table 1.
[0056] Example 2
[0057] Nickel chloride and water glass are added to a dissolving tank 1 filled with deionized water to form a solution containing Ni and Si. The concentration of Ni in the solution is 36 g / L in terms of NiO and the concentration of SiO in the solution is 36 g / L in terms of NiO. 2 The weight concentration is 48 g / L. Nickel chloride, aluminum chloride, and alkylphenol polyoxyethylene (9) ether solutions are added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni, Al, and alkylphenol polyoxyethylene (9) ether. The weight concentration of Ni in the solution containing Ni, Al, and alkylphenol polyoxyethylene (9) ether is 20 g / L in terms of NiO, and the weight concentration of Al in terms of Al 2 O3 The weight concentration is 28g / L, and the molar ratio of the molar number of alkylphenol polyoxyethylene (9) ether to the W in the sodium tungstate solution is 1.2. Among them, the mass ratio of Ni in the solution containing Ni and Si used in the reaction of this embodiment to Ni in the solution containing Ni and Al used is 18:10. The solution containing Ni and Si is placed in the reaction tank 1, and the sodium hydroxide solution (weight concentration is 12%) and the sodium molybdate solution (Mo is MoO 3 The weight concentration of the reaction mixture is 44 g / L) and then dropped into the reaction tank 1 for the first gelling reaction. The gelling temperature is maintained at 55°C. At the end of the reaction, the pH value is controlled at 8.4 and the gelling time is controlled at 1.3 hours. After the reaction is completed, aging is performed. The aging temperature is 80°C and the aging pH value is controlled at 8.1 for 1.4 hours. After the first slurry is obtained, the first slurry is filtered and the obtained filter cake is slurried and mixed evenly with the solution containing Ni, Al and alkylphenol polyoxyethylene (9) ether. First, 600 mL of deionized water and 60 mL of corn oil are added to the reaction tank 2. Then, a sodium carbonate solution with a concentration of 11 wt%, a first slurry filter cake, a solution containing Ni, Al and alkylphenol polyoxyethylene (9) ether, and a sodium tungstate solution (W in WO) are mixed. 3 The weight concentration of the measured solution is 24g / L) and then added to the reaction tank 2 for the second gelling reaction. The gelling temperature is maintained at 58°C, and the initial pH value is controlled to be 13.3. The pH value is adjusted down 6 times to adjust the final pH value to 7.9 at the end. The pH value is adjusted down by 0.9 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry is kept constant for 12 minutes. After the second gelling reaction, aging begins. The aging temperature is 80°C, the pH value is controlled at 8.3, and the aging time is 3.2 hours to obtain the second slurry. The aged slurry is filtered, and the filter cake is dried for the first time, dried at 90°C for 12 hours, rolled, and extruded into a clover shape. After the formed strips are cured at a temperature of 78°C for 45 hours, the temperature is reduced to 18°C, and the curing is continued for 28 hours. Wash with deionized water at room temperature until neutral. The wet strips are then dried at 80°C for 13 hours, and the dried material is roasted at 510°C for 6 hours to obtain catalyst B. The composition and main properties of the catalyst are shown in Table 1.
[0058] Example 3
[0059] Add nickel chloride and water glass to a dissolving tank 1 filled with deionized water to prepare a solution containing Ni and Si. The concentration of Ni in the Ni and Si solution is 20 g / L in terms of NiO and 20 g / L in terms of SiO. 2 The weight concentration is 32g / L. Nickel chloride, aluminum chloride solution and C12 alcohol polyoxyethylene ether are added to the dissolution tank 2 filled with deionized water to prepare a solution containing Ni, Al and C12 alcohol polyoxyethylene ether. The weight concentration of Ni in the solution containing Ni, Al and C12 alcohol polyoxyethylene ether is 28g / L in terms of NiO and 28g / L in terms of Al.2 O 3 The weight concentration is 40g / L, and the molar ratio of the molar number of C12 alcohol polyoxyethylene ether to W in the sodium tungstate solution is 0.8. Among them, the mass ratio of Ni in the solution containing Ni and Si used in the reaction of this embodiment to Ni in the solution containing Ni, Al and C12 alcohol polyoxyethylene ether used is 10:14. The solution containing Ni and Si is placed in the reaction tank 1, and the sodium hydroxide solution (weight concentration is 14%) and the sodium molybdate solution (Mo is MoO 3 The weight concentration of the reaction mixture is 32g / L) and then dropped into the reaction tank 1 for the first gelling reaction. The gelling temperature is maintained at 65°C. The pH value is controlled at 8.0 at the end of the reaction and the gelling time is controlled at 1.1 hours. After the reaction is completed, aging is performed. The aging temperature is 77°C and the aging pH value is controlled at 8.6 for 1.8 hours. After obtaining the first slurry, the filtered filter cake is slurried and mixed evenly with the solution containing Ni, Al and C12 alcohol polyoxyethylene ether. First, 900mL of deionized water and 70mL of peanut oil are added to the reaction tank 2, and then a 14wt% sodium carbonate solution, a first slurry filter cake, a solution containing Ni, Al and C12 alcohol polyoxyethylene ether are mixed into a slurry and a sodium tungstate solution (W is WO 3 The weight concentration of the measured solution is 48g / L) and then added to the reaction tank 2 for the second gelling reaction. The gelling temperature is maintained at 65℃, and the initial pH value is controlled to be 12.9. The pH value is adjusted down 5 times to adjust the final pH value to 7.9 at the end. The pH value is adjusted to 1.0 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry is kept constant for 14 minutes. After the second gelling reaction, aging begins. The aging temperature is 78℃, and the aging pH value is controlled at 8.0. After aging for 2.5 hours, the precipitate slurry continues to be aged under high pressure. The pressure is 13.6MPa, the aging temperature is 160℃, the aging time is 1.1 hours, and the aging pH value is 12.2 to obtain the second slurry. The aged slurry is filtered, the filter cake is dried at 120℃ for 8 hours, rolled, and extruded into a clover shape. The formed strips are cured for 75 hours at a temperature of 55℃. Wash with deionized water at room temperature until neutral. The wet strips were then dried at 75°C for 13.0 hours, and the dried material was calcined at 540°C for 4 hours to obtain Catalyst C. The composition and main properties of the catalyst are shown in Table 1.
[0060] Example 4
[0061] Nickel chloride and water glass are added to a dissolving tank 1 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni and Si solution is 36 g / L in terms of NiO and 36 g / L in terms of SiO. 2The weight concentration is 40g / L. Nickel chloride, aluminum chloride solution and oleyl alcohol polyoxyethylene ether are added to the dissolution tank 2 filled with deionized water to prepare a solution containing Ni, Al and oleyl alcohol polyoxyethylene ether. The weight concentration of Ni in the solution containing Ni, Al and oleyl alcohol polyoxyethylene ether is 28g / L in terms of NiO and 28g / L in terms of Al. 2 O 3 The weight concentration is 36g / L, and the molar ratio of the molar number of oleyl alcohol polyoxyethylene ether to the W in the sodium tungstate solution is 1.2. Among them, the mass ratio of Ni in the solution containing Ni and Si used in the reaction of this embodiment to Ni in the solution containing Ni, Al and oleyl alcohol polyoxyethylene ether used is 9:7. The solution containing Ni and Si is placed in the reaction tank 1, and the sodium hydroxide solution (weight concentration is 12%) and the sodium molybdate solution (Mo is MoO 3 The weight concentration of the reaction mixture is 28g / L) and then dropped into the reaction tank 1 for the first gelling reaction. The gelling temperature is maintained at 75°C. The pH value is controlled at 8.6 at the end of the reaction and the gelling time is controlled at 1.4 hours. After the reaction is completed, aging is performed. The aging temperature is 81°C and the aging pH value is controlled at 8.4 for 1.8 hours. After the first slurry is obtained, the first slurry is filtered and the obtained filter cake is slurried and mixed evenly with the solution containing Ni and Al. First, 600mL of deionized water and 50mL of sunflower oil are added to the reaction tank 2. Then, a 12wt% sodium carbonate solution, a first slurry filter cake, a solution containing Ni, Al and oleyl alcohol polyoxyethylene ether are mixed into a slurry and a sodium tungstate solution (W in WO 3 The weight concentration of the measured product is 32g / L) and then added to the reaction tank 2 for the second gelling reaction. The gelling temperature is maintained at 68°C, and the initial pH value is controlled to be 12.7. The pH value is adjusted down 7 times to adjust the final pH value to 7.1 at the end. The pH value is adjusted down by 0.8 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry is kept constant for 16 minutes. After the second gelling reaction, aging begins. The aging temperature is 82°C, and the aging pH value is controlled at 8.1. The aging is 2.2 hours. Then the precipitate slurry is further aged under high pressure. The pressure is 13.0MPa, the aging temperature is 175°C, the aging time is 1.3 hours, and the aging pH value is 12.0. The second slurry is obtained. The aged slurry is filtered, the filter cake is dried at 80°C for 13 hours, rolled, and extruded into a clover shape. After the formed strips are cured at a temperature of 78°C for 46 hours, the temperature is reduced to 20°C, and the curing is continued for 34 hours. The wet strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 100°C for 9.0 hours and the dried material was calcined at 520°C for 5 hours to obtain catalyst D. The catalyst composition and main properties are shown in Table 1.
[0062] Comparative Example 1
[0063] The reference agent E having the same catalyst composition as that of Example 1 was prepared, and the specific process was as follows:
[0064] According to the catalyst composition of Example 1, nickel chloride, aluminum chloride and water glass were dissolved in deionized water to prepare a mixed solution, wherein the weight concentration of Ni in terms of NiO was 52 g / L, and the weight concentration of Al in terms of Al 2 O 3 The weight concentration is 36g / L, SiO 2 The weight concentration is 36g / L. 500mL of deionized water is added to the reaction tank, and a 10wt% NaOH solution, a sodium molybdate solution (Mo in the form of MoO 3 The weight concentration is 36g / L), sodium tungstate solution (W is WO 3 The weight concentration of the calculated product is 40g / L) and the mixed solution are added to the reaction tank in parallel for gelation. The gelation temperature is maintained at 62°C. At the end, the pH value is controlled at 7.8 and the gelation time is controlled at 1.2 hours to generate a slurry containing nickel and tungsten precipitates. Then the aging is carried out. The aging time is 2.0 hours and the aging temperature is 78°C. The pH value is controlled at 7.5 during aging. After the aging, the reaction slurry is filtered, the filter cake is dried at 100°C for 7 hours, rolled, and extruded into strips. The molded product is washed with deionized water at room temperature, and no molded product is obtained after washing. The powder is dried at 100°C for 12 hours and calcined at 500°C for 4 hours to obtain catalyst E. The composition and main properties of the catalyst are shown in Table 1.
[0065] Comparative Example 2
[0066] According to the method disclosed in CN102049295A, a reference agent F having a catalyst composition similar to that of Example 1 was prepared. The specific process is as follows:
[0067] After adding 1000mL of deionized water to the dissolving tank, nickel chloride, ammonium metatungstate, and aluminum chloride solution were added in sequence, and stirred evenly to form a mixed solution. The weight concentration of Ni in terms of NiO is 52g / L, and the weight concentration of W in terms of WO 3 The weight concentration is 40g / L, Al is expressed as Al 2 O 3The weight concentration is 56g / L. Take 160g of ammonium bicarbonate to prepare an aqueous solution with a molar concentration of 2.5mol / L. Then the mixed solution, the ammonium bicarbonate aqueous solution, and the precipitant 10% ammonia water are added to the reaction tank filled with deionized water to form a gel. The pH value of the gel is 7.8 and the gel temperature is 62°C. After the gel is completed, add the slurry containing SAPO-11 molecular sieve, age for 2 hours, the aging temperature is 78°C, and the pH value is controlled at 7.5 during aging. After aging, filter, add 600mL of deionized water and 36 grams of molybdenum trioxide to the filter cake, beat and stir evenly, filter, and the obtained filter cake is dried at 100°C for 7 hours, then extruded into strips, washed with deionized water until neutral, and the wet strips are dried at 100°C for 12 hours and calcined at 500°C for 4 hours to obtain the final catalyst F. The composition and main properties are shown in Table 1.
[0068] The SAPO-11 molecular sieve used in the comparative example is the one used in CN102049295A, which can be synthesized by conventional methods, such as hydrothermal crystallization method, and has the following properties: SiO 2 / Al 2 O 3 The molar ratio is 0.85, the infrared acid content is 0.9mmol / g, the pore volume is 0.24mL / g, and the specific surface area is 250m 2 / g, particle size is 450nm and crystallinity is 85%.
[0069] Comparative Example 3
[0070] Reference agent G was prepared according to the preparation method of Example 1 (no grease was added to the gelling tank during the second step of gelling) and the catalyst composition.
[0071] Nickel chloride and water glass are added to a dissolving tank 1 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni and Si solution is 28 g / L in terms of NiO and 28 g / L in terms of SiO. 2 The weight concentration is 36g / L. Nickel chloride, aluminum chloride, and octylphenol polyoxyethylene ether solutions are added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni, Al, and octylphenol polyoxyethylene ether. The weight concentration of Ni in the solution containing Ni, Al, and octylphenol polyoxyethylene ether is 24g / L in terms of NiO, and the weight concentration of Al in terms of AlO is 24g / L. 2 O 3 The weight concentration is 36g / L, and the molar ratio of the moles of octylphenol polyoxyethylene ether to the W in the sodium tungstate solution is 0.8. Among them, the mass ratio of Ni in the solution containing Ni and Si used in the reaction of this embodiment to Ni in the solution containing Ni, Al and octylphenol polyoxyethylene ether used is 14:12. The solution containing Ni and Si is placed in the reaction tank 1, and the sodium hydroxide solution (weight concentration is 12%) and the sodium molybdate solution (Mo is in the form of MoO 3The weight concentration of the reaction mixture is 36g / L) and is dropped into the reaction tank 1 for the first gelling reaction. The gelling temperature is maintained at 62°C. The pH value is controlled at 7.8 at the end of the reaction and the gelling time is controlled at 1.2 hours. After the reaction is completed, aging is performed at 78°C and the aging pH value is controlled at 7.5 for 1.8 hours. After obtaining the first slurry, the filter cake is slurried and mixed evenly with the solution containing Ni, Al and octylphenol polyoxyethylene ether. 800mL of deionized water is added to the reaction tank 2, and then a 10wt% sodium carbonate solution, a first slurry filter cake, a solution containing Ni, Al and octylphenol polyoxyethylene ether, and a sodium tungstate solution (W in WO) are mixed. 3 The weight concentration of the measured solution is 40g / L) and then added to the reaction tank 2 for the second gelling reaction. The gelling temperature is maintained at 60℃, and the pH value is initially controlled to be 13.0. The pH value is adjusted to 7.6 at the end by 6 times. The pH value is adjusted to 0.9 each time. After each adjustment to the adjusted value, the pH value of the adjusted reaction slurry is kept constant for 10 minutes. After the second gelling reaction, aging begins. The aging temperature is 78℃, the pH value is controlled at 8.0, and the aging time is 2.5 hours to obtain the second slurry. The aged slurry is filtered, the filter cake is dried at 100℃ for 7 hours, rolled, and extruded into a clover shape. After the formed strips are cured at a temperature of 70℃ for 50 hours, the temperature is reduced to 20℃, and the curing is continued for 30 hours. Wash with deionized water at room temperature until neutral. The wet strips are then dried at 100℃ for 12.0 hours, and the dried material is calcined at 500℃ for 4 hours to obtain catalyst G. The composition and main properties of the catalyst are shown in Table 1.
[0072] Comparative Example 4
[0073] Reference agent H was prepared according to the preparation method of Example 1 (no silicon was added when preparing mixed solution A).
[0074] Nickel chloride and aluminum chloride are added to a dissolving tank 1 filled with deionized water to prepare a solution containing Ni and Al. The weight concentration of Ni in the Ni and Al solutions is 28 g / L as NiO and 28 g / L as Al. 2 O 3 The nickel chloride, aluminum chloride and octylphenol polyoxyethylene ether solutions were added to the dissolution tank 2 filled with deionized water to prepare a solution containing Ni, Al and octylphenol polyoxyethylene ether. The weight concentration of Ni in the solution containing Ni, Al and octylphenol polyoxyethylene ether was 24 g / L in terms of NiO and 24 g / L in terms of Al. 2 O 3The weight concentration is 36g / L, and the molar ratio of the molar number of octylphenol polyoxyethylene ether to the W in the sodium tungstate solution is 0.8. Among them, the mass ratio of Ni in the solution containing Ni and Al used in the reaction of this embodiment to Ni in the solution containing Ni, Al and octylphenol polyoxyethylene ether used is 14:12. The solution containing Ni and Al is placed in the reaction tank 1, and the sodium hydroxide solution (weight concentration is 12%) and the sodium molybdate solution (Mo is in the form of MoO 3 The weight concentration of the reaction mixture is 36 g / L) and is dropped into the reaction tank 1 for the first gelling reaction. The gelling temperature is maintained at 62°C. The pH value is controlled at 7.8 at the end of the reaction and the gelling time is controlled at 1.2 hours. After the reaction is completed, aging is performed at 78°C and the aging pH value is controlled at 7.5 for 1.8 hours. After obtaining the first slurry, the filter cake is slurried and mixed evenly with the solution containing Ni, Al and octylphenol polyoxyethylene ether. 800 mL of deionized water and 60 mL of rapeseed oil are added to the reaction tank 2, and then a 10 wt% sodium carbonate solution, a first slurry filter cake, a solution containing Ni, Al and octylphenol polyoxyethylene ether, and a sodium tungstate solution (W in WO) are mixed. 3 The weight concentration of the measured solution is 40g / L) and then added to the reaction tank 2 for the second gelling reaction. The gelling temperature is maintained at 60℃, and the pH value is initially controlled to be 13.0. The pH value is adjusted to 7.6 at the end by 6 times. The pH value is adjusted to 0.9 each time. After each adjustment to the adjusted value, the pH value of the adjusted reaction slurry is kept constant for 10 minutes. After the second gelling reaction, aging begins. The aging temperature is 78℃, the pH value is controlled at 8.0, and the aging time is 2.5 hours to obtain the second slurry. The aged slurry is filtered, the filter cake is dried at 100℃ for 7 hours, rolled, and extruded into a clover shape. After the formed strips are cured at a temperature of 70℃ for 50 hours, the temperature is reduced to 20℃, and the curing is continued for 30 hours. Wash with deionized water at room temperature until neutral. The wet strips are then dried at 100℃ for 12.0 hours, and the dried material is calcined at 500℃ for 4 hours to obtain catalyst H. The composition and main properties of the catalyst are shown in Table 1.
[0075] Comparative Example 5
[0076] According to the method of Example 1, Catalyst I was prepared according to the component content ratio of Catalyst A in Table 1, and the formed strips were not subjected to desalination treatment.
[0077] Nickel chloride and water glass are added to a dissolving tank 1 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni and Si solution is 28 g / L in terms of NiO and 28 g / L in terms of SiO. 2The weight concentration is 36g / L. Nickel chloride, aluminum chloride, and octylphenol polyoxyethylene ether solutions are added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni, Al, and octylphenol polyoxyethylene ether. The weight concentration of Ni in the solution containing Ni, Al, and octylphenol polyoxyethylene ether is 24g / L in terms of NiO, and the weight concentration of Al in terms of AlO is 24g / L. 2 O 3 The weight concentration is 36g / L, and the molar ratio of the moles of octylphenol polyoxyethylene ether to the W in the sodium tungstate solution is 0.8. Among them, the mass ratio of Ni in the solution containing Ni and Si used in the reaction of this embodiment to Ni in the solution containing Ni, Al and octylphenol polyoxyethylene ether used is 14:12. The solution containing Ni and Si is placed in the reaction tank 1, and the sodium hydroxide solution (weight concentration is 12%) and the sodium molybdate solution (Mo is in the form of MoO 3 The weight concentration of the reaction mixture is 36 g / L) and is dropped into the reaction tank 1 for the first gelling reaction. The gelling temperature is maintained at 62°C. The pH value is controlled at 7.8 at the end of the reaction and the gelling time is controlled at 1.2 hours. After the reaction is completed, aging is performed at 78°C and the aging pH value is controlled at 7.5 for 1.8 hours. After obtaining the first slurry, the filter cake is slurried and mixed evenly with the solution containing Ni, Al and octylphenol polyoxyethylene ether. 800 mL of deionized water and 60 mL of rapeseed oil are added to the reaction tank 2, and then a 10 wt% sodium carbonate solution, a first slurry filter cake, a solution containing Ni, Al and octylphenol polyoxyethylene ether, and a sodium tungstate solution (W in WO) are mixed. 3 The weight concentration of the calculated solution is 40g / L) and then added to the reaction tank 2 for the second gelling reaction. The gelling temperature is maintained at 60°C, and the initial pH value is controlled to be 13.0. The pH value is adjusted down 6 times to adjust the final pH value to 7.6 at the end. The pH value is adjusted down by 0.9 each time. After each adjustment to the adjusted value, the pH value of the adjusted reaction slurry is kept constant for 10 minutes. After the second gelling reaction, aging begins. The aging temperature is 78°C, the pH value is controlled at 8.0, and the aging time is 2.5 hours to obtain the second slurry. The aged slurry is filtered, the filter cake is dried at 100°C for 7 hours, rolled, and extruded into a clover shape. Wash with deionized water at room temperature, and no molded product is obtained after washing. The powder is dried at 100°C for 12.0 hours, and the dried material is calcined at 500°C for 4 hours to obtain catalyst I. The catalyst composition and main properties are shown in Table 1.
[0078] Comparative Example 6
[0079] According to the preparation method disclosed in CN106513006A, a reference agent J having a catalyst composition similar to that of Example 1 of the present invention was prepared. The specific process is as follows:
[0080] Nickel carbonate and 300 ml of deionized water were uniformly mixed and added to a 1L high-pressure ultrasonic reactor. The ultrasonic frequency was set to 60 KHz, and the mixture was heated to 80°C. After the temperature was kept constant for 1 hour, the ultrasonic frequency was reduced to 20 KHz, the system temperature was increased to 120°C, ammonium molybdate and 3 g of polyvinyl pyrrolidone were added, and then 10 ml of 25 wt% ammonia water was added dropwise to the system. After the temperature was kept constant for 2 hours, the ultrasound was turned off, the stirring was turned on, the speed was 300 rpm, ammonium metatungstate was added, and then citric acid was added until the pH of the system was 4.2. After the temperature was kept constant for 2 hours, the heating was turned off, and the slurry was collected after the system was cooled to room temperature. The slurry was spray dried, and the inlet temperature and outlet temperature were controlled at about 200°C and 100°C, respectively. The obtained dry powder was roasted at 330°C in a muffle furnace for 3 hours to obtain the active component powder. The active component powder was mixed with aluminum hydroxide dry gel, and then a 10% dilute nitric acid aqueous solution was added for kneading and extrusion to obtain a strip. The strip was dried at 110°C for 10 h and calcined in a muffle furnace at 400°C for 5 h to obtain a reference agent J. The catalyst composition and main properties are shown in Table 1.
[0081] Comparative Example 7
[0082] According to the preparation method disclosed in CN1951558A, reference agent K was prepared as follows:
[0083] Add deionized water to the dissolving tank, add nickel chloride, ammonium metatungstate and aluminum chloride to dissolve, and prepare acidic working solution A. The weight concentration of Ni in solution A is 74.8 g / L in terms of NiO, and the weight concentration of W in terms of WO 3 The weight concentration is 48.6 g / L, Al is expressed as Al 2 O 3 The weight concentration of the solution is 44g / L, and the pH value of solution A is 1.8. 350mL of deionized water was added to the reaction tank, and the temperature was raised to 62°C. Under stirring, solution A and 10wt% ammonia water were added to the reaction tank in parallel to form gel. The gelling temperature was 62°C, the gelling time was 1 hour, and the pH value of the slurry during the gelling process was 8.5. After the gelling was completed, it was aged for 2 hours at a temperature of 75°C, and the pH value was controlled at 7.6 during aging. Then filter, add 600mL of deionized water and 32.6g of molybdenum trioxide to the filter cake, beat and stir evenly, filter, dry the filter cake at 100°C for 7 hours, roll, and extrude into a cylindrical shape. Wash with deionized water at room temperature until neutral. Then the wet strips were dried at 100°C for 12 hours and calcined at 500°C for 4 hours to obtain catalyst K. The composition and main properties of the catalyst are shown in Table 1.
[0084] Example 5
[0085] This example is an activity evaluation experiment of the catalyst of the present invention, and is compared with the catalyst of the comparative example. From the physicochemical properties of the catalyst in Table 1, it can be seen that when the raw materials contain more sodium raw materials during the preparation process, the catalysts A, B, C of the present invention and the comparative catalysts F, G, H, J, K are used for washing (the comparative catalysts E and I are washed into powders without activity evaluation), and a comparative evaluation test is carried out on a 200mL small hydrogenation device. The mixed diesel (the weight ratio of straight-run diesel, coking diesel, and catalytic diesel is 28:20:52) is the test raw material. The process conditions for the evaluation of catalyst activity are: hydrogen partial pressure of 6.4MPa, reaction temperature of 365°C, liquid hourly volume space velocity of 2.0h -1 , the volume ratio of hydrogen to oil is 500:1, and the main properties of the raw materials are shown in Table 4. The results of catalyst activity evaluation are shown in Table 5. The types of sulfides in the hydrorefined oil were detected by gas chromatography-atomic emission spectrometry detector (GC-AED), and the results are shown in Table 6.
[0086] It can be seen from Table 1 that when the catalyst of the present invention uses a relatively high sodium-containing raw material in the preparation process, the catalyst has good crushing strength after desalting and washing after molding, while without desalting, the molded catalyst strips become powder after washing.
[0087] It can be seen from the evaluation results that compared with the comparative example catalyst, the catalyst of the present invention shows high hydrodesulfurization activity when removing difficult-to-treat 4,6-DMDBT macromolecular sulfides, and has excellent ultra-deep hydrodesulfurization activity. At the same time, the diesel product has a good yield. When the activity evaluation reaction space velocity is increased, the catalyst of the present invention still has excellent ultra-deep desulfurization activity by increasing the reaction temperature. Compared with the evaluation results of the comparative example catalyst, the catalyst of the present invention effectively reduces the influence of thermodynamic equilibrium on the high-temperature hydrogenation pathway and has good temperature adaptability. The hydrorefining catalyst of the present invention has a large pore volume and specific surface area, and the pore distribution is mainly concentrated above 10nm. The catalyst of the present invention is used for processing light distillate oil, especially for processing inferior diesel fractions, and has excellent ultra-deep hydrodesulfurization and denitrification performance.
[0088] Table 1 Composition and properties of catalysts prepared in Examples and Comparative Examples
[0089] Catalyst No. A B C D NiO, wt% 26 28 24 32 <![CDATA[WO 3 ,wt%]]> 20 12 24 16 <![CDATA[MoO 3 ,wt%]]> 18 22 16 14 <![CDATA[SiO 2 ,wt%]]> 18 24 16 20 <![CDATA[Al 2 O 3 ,wt%]]> 18 14 20 18 <![CDATA[Na 2 O,%]]> 0.074 0.076 0.079 0.063 <![CDATA[Specific surface area, m 2 / g]]> 298 291 308 317 Pore volume, mL / g 0.415 0.406 0.426 0.439 Pore distribution <4nm 5.31 5.98 5.17 5.03 4nm~10nm 21.03 21.52 20.51 19.59 10nm~15nm 41.85 41.24 42.18 42.66 >15nm 31.81 31.26 32.14 32.72 Mechanical strength, N / mm 19.4 19.7 19.4 19.2
[0090] Table 1 (Continued) Catalyst compositions and properties prepared in Examples and Comparative Examples
[0091] Catalyst No. E F G H I J K NiO, wt% 26 26 26 26 26 26 37.4 <![CDATA[WO 3 ,wt%]]> 20 20 20 20 20 20 24.3 <![CDATA[MoO 3 ,wt%]]> 18 18 18 18 18 18 16.3 <![CDATA[SiO 2 ,wt%]]> 18 4 18 - 18 - - <![CDATA[Al 2 O 3 ,wt%]]> 18 28 18 36 18 36 22 <![CDATA[P 2 O 5 ,wt%]]> - 4 - - - - - <![CDATA[Na 2 O,%]]> 0.34 0.14 0.099 0.075 0.52 0.13 0.13 <![CDATA[Specific surface area, m 2 / g]]> 142 199 264 295 239 283 174 Pore volume, mL / g 0.232 0.252 0.374 0.410 0.342 0.385 0.301 Pore distribution <4nm 62.81 22.82 11.31 3.52 16.22 38.21 46.87 4nm~10nm 30.52 71.44 32.42 23.83 41.18 48.61 40.72 10nm~15nm 4.37 4.50 36.83 41.11 28.23 7.28 8.26 >15nm 2.30 1.24 19.44 31.54 14.37 5.90 4.15 Mechanical strength, N / mm - 17.6 18.9 18.8 - 13.5 19.1
[0092] Table 2 Composite oxide composition in the core and shell of the catalyst obtained in each example (based on the catalyst mass)
[0093] Catalyst No. A B C D G H I Composite oxide composition in the core NiO, wt% 14 18 10 18 16 14 14 <![CDATA[MoO 3 ,wt%]]> 18 22 16 14 12 18 18 <![CDATA[SiO 2 ,wt%]]> 18 24 16 20 12 - 18 <![CDATA[WO 3 ,wt%]]> - - - - 6 - - <![CDATA[Al 2 O 3 ,wt%]]> - - - - 4 18 - Composite oxide composition in shell NiO, wt% 12 10 14 14 8 12 12 <![CDATA[WO 3 ,wt%]]> 20 12 24 16 14 20 20 <![CDATA[Al 2 O 3 ,wt%]]> 18 14 20 18 14 18 18 <![CDATA[MoO 3 ,wt%]]> - - - - 6 - - <![CDATA[SiO 2 ,wt%]]> - - - - 6 - -
[0094] Table 3 Average particle size and particle size distribution of the catalyst core-shell composite oxide particles obtained in each example
[0095] Catalyst No. A B C D E F Average particle size of core-shell composite oxide particles, nm 9.7 9.9 10.1 10.2 33.6 23.8 Particle size distribution of core-shell composite oxide particles, % Particle size less than 7nm 6.34 6.26 6.13 6.25 3.32 4.05 Particle size is 7nm-13nm 84.32 84.13 84.08 83.92 21.22 28.19 Particle size greater than 13nm 9.34 9.61 9.79 9.83 77.46 67.76
[0096] Table 3 (Continued) Average particle size and particle size distribution of the catalyst core-shell composite oxide particles obtained in each example
[0097] Catalyst No. G H I J K Average particle size of core-shell composite oxide particles, nm 33.7 10.0 11.9 24.4 19.4 Particle size distribution of core-shell composite oxide particles, % Particle size less than 7nm 2.23 6.03 6.12 8.93 8.42 Particle size is 7nm-13nm 20.42 83.82 81.47 28.46 33.62 Particle size greater than 13nm 77.35 10.15 12.41 62.61 57.96
[0098] Table 4 Main properties of crude oil
[0099] project Analyze the results <![CDATA[Density (20 °C), g / cm 3 > 0.8897 Distillation range, ℃ 175-379 S, µg / g 13100 N, µg / g 922
[0100] Table 5 Catalyst activity evaluation results
[0101] Catalyst No. A B C F G H J K <![CDATA[Generated oil density (20 °C), g / cm 3 > 0.8631 0.8633 0.8635 0.8656 0.8712 0.8649 0.8772 0.8707 S, µg / g 7.0 7.2 7.5 38.2 128.3 38.5 236.8 118.8 N, µg / g 3.0 3.1 3.3 16.4 67.8 14.6 112.8 62. 2 Diesel yield, % 99.2 99.1 99.0 86.6 98.8 99.1 98.3 98.9
[0102] Table 6 Content of different sulfides in hydrorefined oil
[0103] Catalyst No. A B C F G H J K Sulfur content in hydrorefined oil, µg / g 7.0 7.2 7.5 38.2 128.3 38.5 236.8 118.8 <![CDATA[C 1 -DBT,µg / g]]> 0 0 0 3.2 11.1 4.8 22.1 9.1 4- MDBT, µg / g 1.5 1.5 1.6 8.1 27.2 8.0 52.2 25.4 6-MDBT, µg / g 1.9 2.0 2.1 9.6 30.7 9.1 60.2 26.3 4,6-DMDBT, µg / g 3.6 3.7 3.8 17.3 59.3 16.6 102.3 58.0
Claims
1. A method for preparing a bulk hydrotreating catalyst, characterized in that The method comprises the following steps: (1) subjecting a sodium hydroxide aqueous solution, a sodium molybdate solution and a solution containing nickel and silicon to a first gelling reaction, and then subjecting the solution to aging to obtain a first slurry, filtering to obtain a filter cake, and beating and mixing the filter cake with a solution containing nickel, aluminum and a polyoxyethylene nonionic surfactant to obtain a mixed slurry; (2) adding deionized water and unsaturated higher fatty acid glyceride to a reactor, and then concurrently adding a sodium tungstate solution, a sodium carbonate or sodium bicarbonate aqueous solution and the mixed slurry obtained in step (1) to the reactor to perform a second gelling reaction, and the reaction is carried out. After aging, a second slurry is generated; (3) the second slurry is aged, and after the aging is completed, the solid-liquid separation is carried out, and the solid phase is dried and formed to obtain a molded product; (4) the molded product is desalted, washed, dried and calcined to obtain a bulk hydrogenation refining catalyst; in the second gelling reaction of step (2), the pH value is adjusted from the initial value to the final pH value by a stepwise reduction method, and the stepwise reduction method is to reduce the pH value to the required value at that time, and keep the pH value of the reaction slurry constant until the next reduction begins, and the number of reductions is 2 to 10 times.
2. The method according to claim 1, characterized in that: In the nickel-silicon solution described in step (1), the weight concentration of nickel calculated as nickel oxide is 5-120 g / L, and the weight concentration of silicon calculated as silicon dioxide is 2-80 g / L. When preparing the nickel-silicon solution, the nickel source used is one or more of nickel sulfate, nickel nitrate, and nickel chloride, and the silicon source is one or more of water glass, silica sol, and sodium silicate. In the sodium molybdate solution described in step (1), the weight concentration of molybdenum calculated as molybdenum trioxide is 5-110 g / L. The weight concentration of the sodium hydroxide aqueous solution described in step (1) is 5%-30%.
3. The method according to claim 1, characterized in that: The conditions of the first gelling reaction in step (1) are: reaction temperature of 30-90° C., pH value of 7.0-11.0, and gelling time of 0.2-2.5 hours.
4. The method according to claim 1, characterized in that: The aging conditions of step (1) are as follows: aging temperature is 60-90° C., pH value is 7.0-11.0, and aging time is 0.3-2.5 hours.
5. The method according to claim 1, characterized in that: In the nickel, aluminum and polyoxyethylene nonionic surfactant solution of step (1), the weight concentration of nickel calculated as nickel oxide is 5-110 g / L, and the weight concentration of aluminum calculated as aluminum oxide is 2-95 g / L; the molar ratio of the polyoxyethylene nonionic surfactant to the sodium tungstate solution calculated as tungsten is 0.3-2.5:
1.
6. The method according to claim 1, characterized in that: The polyoxyethylene nonionic surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and dodecylamine polyoxyethylene ether.
7. The method according to claim 1, characterized in that: In step (1), the weight of nickel introduced through the solution containing nickel and silicon accounts for 30% to 80% of the total nickel weight of the hydrotreating catalyst obtained in step (4); the weight of nickel introduced through the solution containing nickel, aluminum and polyoxyethylene nonionic surfactant accounts for 20% to 70% of the total nickel weight in the hydrotreating catalyst obtained in step (4).
8. The method according to claim 1, characterized in that: In the sodium tungstate solution described in step (2), the weight concentration of tungsten in terms of tungsten trioxide is 4-140 g / L.
9. The method according to claim 1, characterized in that: The volume ratio of the deionized water added in step (2) to the first slurry in step (1) is 0.1:1 to 3:
1.
10. The method according to claim 1, characterized in that: The unsaturated higher fatty acid glyceride described in step (2) is one or more of peanut oil, rapeseed oil, cottonseed oil, sunflower seed oil, soybean oil, corn oil, tea oil and olive oil; the volume ratio of the unsaturated higher fatty acid glyceride to deionized water is 1:60~1:
4.
11. The method according to claim 1, characterized in that: The conditions of the second gelling reaction in step (2) are as follows: the reaction temperature is 30-90° C., the initial pH value is controlled at 10.0-14.0, the final pH value is 7.0-8.5 at the end, and the gelling reaction time is 0.5-6.0 hours.
12. The method according to claim 1, characterized in that: The aging conditions in step (2) are as follows: aging temperature is 40 to 90° C., aging time is 1 to 5 hours, and pH value is 7.0 to 11.
0.
13. The method according to claim 1, characterized in that: The aging in step (2) is carried out as follows: the first step is normal pressure aging: the aging temperature is 30-90°C, the aging time is 1-6 hours, and the pH value is 6.5-10.0; the second step is high pressure aging: the temperature is 100-195°C, the time is 0.1-3.5 hours, the pressure is not less than 10 MPa, and the pH value is 10.0-13.
0.
14. The method according to claim 1, characterized in that: During the molding process described in step (3), an extrusion aid and a peptizing agent are added, wherein the extrusion aid is one or more of sesbania powder, carbon black, graphite powder or cellulose, and the peptizing agent is an acid solution containing one or more of hydrochloric acid, sulfuric acid and acetic acid, and the amount of the extrusion aid accounts for 1wt% to 10wt% of the total material dry basis; the catalyst is prepared into flake, spherical, cylindrical and special-shaped strip shapes as required.
15. The method according to claim 1, characterized in that: The desalination process described in step (4) is: first curing, then washing to remove the salt precipitated on the surface of the molded product, the curing conditions are a temperature of 5 to 100° C. and a time of 10 to 100 hours.
16. The method according to claim 1, characterized in that: The desalination treatment in step (4) is carried out as follows: the first stage is carried out at a temperature of 60 to 90°C for curing for 5 to 60 hours; the second stage is carried out at a temperature of 10 to 30°C for 1 to 48 hours; and then washing is performed to remove the precipitated salt.
17. A bulk hydrotreating catalyst prepared by the method according to any one of claims 1 to 16, characterized in that: The catalyst is a composite amorphous oxide particle with a core-shell structure, wherein the core phase is an amorphous composite oxide containing molybdenum, nickel and silicon, and the shell phase is an amorphous composite oxide containing tungsten, nickel and aluminum; the average particle size of the catalyst particles is 8-13 nm; the particle size distribution of the catalyst particles is as follows: the number of particles with a particle size less than 7 nm accounts for 2%-15% of the total number of particles, the number of particles with a particle size of 7 nm-13 nm accounts for 66%-88% of the total number of particles, and the number of particles with a particle size greater than 13 nm accounts for 3%-21% of the total number of particles; the pore size distribution of the bulk hydrorefining catalyst is as follows: the pore volume occupied by pores with a diameter of less than 4 nm accounts for 1%-10% of the total pore volume, the pore volume occupied by pores with a diameter of 4-10 nm accounts for 12%-40% of the total pore volume, the pore volume occupied by pores with a diameter of 10-15 nm accounts for 22%-56% of the total pore volume, and the pore volume occupied by pores with a diameter of more than 15 nm accounts for 18%-45% of the total pore volume.
18. The bulk hydrotreating catalyst according to claim 17, characterized in that: Based on the mass of the core-shell structured composite oxide particles, the core phase accounts for 20%-90%, and the shell phase accounts for 10%-80%; the atomic molar ratio of molybdenum to nickel in the core phase is 1:28-12:1, and the content of silicon in terms of silicon dioxide accounts for 2%-38% of the mass of the catalyst; the atomic molar ratio of tungsten to nickel in the shell phase is 1:22-8:1, and the content of aluminum in terms of aluminum oxide accounts for 5%-36% of the mass of the catalyst; the mass of nickel oxide in the core phase accounts for 30%-80% of the total mass of nickel oxide in the hydrorefining catalyst, and the mass of nickel oxide in the shell phase accounts for 20%-70% of the total mass of nickel oxide in the hydrorefining catalyst; the content of Na2O in the catalyst is less than 0.12%.
19. Use of the bulk hydrotreating catalyst according to claim 17 in the hydrotreating reaction of inferior distillate oil.
Citation Information
Patent Citations
Super-deep fraction oil hydrodesulphurization catalyst and preparation method thereof
CN102049295A
Method for preparing hydrogenation catalyst composition
CN102451706A
A hydrofining catalyst and its preparation method
CN106179474B
Preparation method of bulk-phase hydrofining catalyst
CN106513006A
Method for preparing hydrofining catalyst
CN110038581A